Clinical usefulness of end‐tidal CO2 measured using a portable capnometer in patients with respiratory disease. (6th January 2023) - Suzuki, Manabu; Fujimoto, Shota; Sakamoto, Keita; Tamura, Kentaro; Ishii, Satoru; Iikura, Motoyasu; Izumi, Shinyu; Takeda, Yuichiro; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: Introduction: This study aimed to evaluate the correlation and agreement between end‐tidal CO2 (EtCO2 ) measured with the novel portable capnometer (CapnoEye®) and partial pressure of arterial carbon dioxide (PaCO2 ) levels in patients with respiratory diseases and to compare the efficacy of EtCO2 and PvCO2 in predicting PaCO2 levels. Methods: We analyzed the correlation and the agreement between EtCO2 and PaCO2 and between PvCO2 and PaCO2 using Pearson's moment correlation coefficient in patients with type 1 and type 2 respiratory failure and both groups overall. Results: A total of 100 samples were included that comprised 67 men (67%). The mean age of the subjects was 77 ± 13 years. Chronic obstructive pulmonary disease (COPD) (43%) was the most common disease. There was a high correlation between EtCO2 and PaCO2 ( r = 0.88; p < 0.0001). Sixty‐six PvCO2 samples were obtained, and there was a high correlation between PvCO2 and PaCO2 ( r = 0.81; p < 0.0001). Regarding type 2 respiratory failure, there was a high correlation between EtCO2 and PaCO2 ( r = 0.81). The Bland–Altman analysis between PaCO2 and EtCO2 revealed a bias of 5.7 mmHg, with limits of agreement ranging from −5.1 mmHg to 16.5 mmHg. In contrast, the analysis between PaCO2 and PvCO2 revealed a bias of −6.8 mmHg, and the limits of agreement ranged from −22.13 mmHg to 8.53 mmHg. Conclusion: EtCO2 measured by CapnoEye® was significantly correlated to PaCO2 levels in patients with respiratory diseases. Moreover, CapnoEye® may be more useful for predicting hypercapnia conditions in which respiratory diseases are compared with measure PvCO2 . Abstract : EtCO2 measured by CapnoEye® was significantly correlated to PaCO2 levels in patients with respiratory diseases. While type 1 patients displayed a moderate correlation, type 2 patients demonstrated a high correlation between EtCO2 and PaCO2 . In contrast, the correlation between PvCO2 and PaCO2 was moderate for both type 1 and type 2. CapnoEye® may be more useful for predicting hypercapnia conditions in which respiratory diseases are compared with measure PvCO2 .